Manejo integrado de Thrips tabaci Lindeman en Allium cepa L. en Virú, La Libertad - Chaupe García, Cristhian Emanuel (2019)
The present research work was carried out in the area of Virú, Latitude -8.53917, Longitude: -78.6789, 8 ° 32'21'' South, 78 ° 40'44'' West, La Libertad. The objective was: Stablish an integrated management for Thrips tabaci Lindeman in Allium cepa L. in Virú, La Libertad. The methodology was descriptive, the information was obtained through personalized visits and interviews, supplemented by surveys to 5 producers. The study was based on two phases: Establishment of the baseline according to technical aspects such as knowledge of agroecosystems and cultivation, territorial aspects: Interactions between ecosystems, extension and size, socio-economic aspects. The Integrated Management of Thrips tabaci Lindeman was established based on the results obtained in the baseline. It was concluded that the Thrips tabaci Lindeman integrated management includes cultural control methods such as: field design, application of organic matter, irrigation management, proper fertilization management, broadleaf weed control and fences maintenance, ; biological control methods such as: releases of predatory insects such as Chrysoperla spp; ethological control to evaluate population dynamics using glued and phototropic chromotropic traps, among others; chemical control method such as the use of insecticides of the group of neonocotenoids, Imidacloprid at 0.1% and in high infestations Spitrotetramat at 0.2%.